Carbon particle composite material, flexible electrode material, flexible electrode and preparation method and application thereof

By combining carbon particles with gallium oxide to form a composite material with gallium-based liquid metal, the corrosion and compatibility problems of conductive materials are solved, and high conductivity and stability are achieved. It is suitable for the application of flexible electronic skin and soil pressure gauge .

CN119191280APending Publication Date: 2024-12-27CHONGQING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411449978.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing gallium-based liquid metals are easily corroded in conductive materials, resulting in reduced conductivity and magnetic response performance, difficult to be compatible with carbon particles, and cannot meet the high conductivity requirements of flexible electrode materials.

Method used

Carbon particles and gallium oxide composite materials are used to purify carbon particles by oil bath heating in acid solution and hydrothermal reaction, and calcined under nitrogen environment to form gallium oxide carbon nanotubes or graphene composite materials mixed with liquid metal to prepare flexible electrode materials , avoid corrosion and improve conductivity.

Benefits of technology

It achieves good compatibility between carbon particles and liquid metals, maintains high conductivity, is suitable for sensitive components of flexible electronic skin and soil pressure gauge, and has short response time, high sensitivity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191280A_ABST
    Figure CN119191280A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon particle composite material, a flexible electrode material, a flexible electrode and a preparation method and application thereof, and belongs to the technical field of composite materials. The carbon particle composite material comprises carbon particles and gallium oxide, and gallium oxide is attached to the surfaces of the carbon particles. The flexible electrode material comprises the following components in parts by mass: 2-17 parts of gallium-plated carbon particles and 83-98 parts of liquid metal. According to the flexible electrode, a flexible substrate is coated with the flexible electrode material through silk-screen printing, copper conductive wires are pasted to the two ends of the printed flexible electrode material, the surface of the flexible electrode material is coated with the viscous-elastic material coating glue, and the flexible electrode is obtained through room-temperature curing and drying. And preparing an electronic skin and earth pressure gauge sensitive element. The composite material disclosed by the invention can be applied to electronic skin for detecting the motion state of a human body and a soil pressure meter for monitoring soil pressure in engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new materials and application technologies, and specifically relates to a carbon particle composite material, a flexible electrode material, a flexible electrode and a preparation method and application thereof. The flexible electrode material is used to prepare flexible electronic skin and sensitive elements of an earth pressure gauge. Background Art

[0002] The basis of intelligence is to accurately and quickly perceive the external environment. Flexible electrodes are an important detection method to achieve this function. Their application areas include artificial intelligent skin, biomedicine, bionic flexible actuators, flexible electronics, robotics, engineering monitoring and many other fields. At present, gallium-based liquid metal is widely used in the manufacture of flexible electrodes because of its high conductivity, self-healing ability, non-toxicity and unique surface chemical properties. However, due to the huge interfacial tension of liquid metal, liquid metal has strong fluidity, and under normal conditions, the surface of liquid metal has a unique metal oxide layer.

[0003] In order to solve the above problems, Chinese patent document CN 116555655 A discloses a modified gallium-based liquid metal paste and a preparation method, in which magnetic metal powder is evenly dispersed into liquid metal under an inert gas atmosphere to prepare a liquid metal paste that can be directly used. Although the inert gas atmosphere can prevent the liquid metal from forming an oxide layer and promote the metal powder to enter the liquid metal, the liquid metal in the liquid metal paste will corrode the metal powder and affect the electrical conductivity, thermal conductivity and magnetic response performance of the liquid metal paste. In this regard, there is a document “FeNbVB Alloy Particles Suspended in Liquid Gallium: Investigating the Magnetic Properties of the MR Suspension”, G. Dodbiba, K. Ono, HS Park, S. Matsuo, and T. Fujita, International Journal of Modern Physics B. 2011, 25:07, 947-955. DOI: 10.1142 / s0217979211058444 (Liquid Gallium Doped FeNbVB Alloy Particles: Investigation of Magnetic Properties of Magnetorheological Fluids, G. Dodbiba, K. Ono, HS Park, S. Matsuo, and T. Fujita, International Journal of Modern Physics B. 2011, 25:07, 947-955. DOI:10.1142 / s0217979211058444) records: A layer of SiO2 with high compatibility with liquid metal is plated on the surface of FeNbVB. 2, which promotes FeNbVB to be easily mixed with liquid metal in normal atmospheric environment, but due to SiO 2 Due to the insulating properties, this method reduces the conductivity of the liquid metal paste and does not meet the high conductivity requirements of flexible electrode materials. Summary of the invention

[0004] In view of the problem that existing conductive materials are corroded in liquid metal, the technical problem to be solved by the present invention is to provide a carbon particle composite material, which can overcome the difficulty that carbon particles are incompatible with liquid metal and avoid the corrosion of additives by liquid metal. The present invention also provides a flexible electrode material, which has softness, short response time, high sensitivity and high stability. The present invention also provides a method for preparing a carbon particle composite material, a flexible electrode and a method for preparing a flexible electrode, and an application of a flexible electrode.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: In a first aspect, the present invention provides a carbon particle composite material, comprising carbon particles and gallium oxide, wherein gallium oxide is attached to the surface of the carbon particles, and the carbon particles are carbon nanotubes or graphene.

[0006] In a second aspect, the present invention provides a method for preparing a carbon particle composite material, comprising the following steps: Step 1, purifying carbon particles: heating carbon particles in an acidic solution through an oil bath and obtaining purified carbon particles in a condensation reflux tube of water at room temperature to eliminate impurities and disperse carbon nanotubes; Step 2, composite gallium oxide on the surface of carbon particles: add purified carbon particles and gallium chloride into ultrapure water, transfer to a reactor for hydrothermal reaction to obtain a gallium oxide carbon nanotube composite material, and then calcine in a tubular furnace under a nitrogen environment to obtain a gallium oxide carbon particle composite material with higher crystallinity.

[0007] The acid solution is a nitric acid solution or a hydrochloric acid solution, and the hydrogen ion concentration is 1M to 3M.

[0008] In a third aspect, the present invention provides a flexible electrode material which is a mixture of 2 to 17 parts of a gallium oxide carbon particle composite material and 83 to 98 parts of a liquid metal, wherein the liquid metal is a gallium-indium alloy or a gallium-indium-tin alloy.

[0009] In a fourth aspect, the present invention provides a flexible electrode prepared using the above-mentioned flexible electrode material, wherein the flexible electrode material is coated on a flexible substrate by screen printing, copper conductive wires are pasted on both ends of the printed flexible electrode material, a viscoelastic material coating glue is coated on the surface of the flexible electrode material, and the flexible electrode is cured and dried at room temperature to obtain a flexible electrode.

[0010] In a fifth aspect, the present invention provides a method for preparing a flexible electrode, comprising the following steps: Step A, preparing a liquid metal paste: mixing 2 to 17 parts by mass of a gallium oxide carbon particle composite material and 83 to 98 parts by mass of a liquid metal to obtain a liquid metal paste; Step B, preparing a flexible electrode: coating the liquid metal paste on the surface of a flexible substrate by screen printing to obtain a flexible electrode; Step C, making a single electrode: sticking a wire to the end of the liquid metal paste, coating a viscoelastic material on the surface of the liquid metal paste, and drying at room temperature to obtain a packaged single electrode.

[0011] In a sixth aspect, the flexible electrode provided by the present invention is used as electronic skin to detect the movement state of the human body.

[0012] In a seventh aspect, the flexible electrode provided by the present invention is used as a sensitive element of an earth pressure gauge to measure earth pressure.

[0013] In an eighth aspect, the present invention provides an earth pressure gauge, comprising a cylindrical outer shell, a connecting cylinder, a gasket, the above-mentioned flexible electrode and a bottom cover which are arranged in sequence from top to bottom in the inner cavity of the outer shell, the connecting cylinder being located in the center part between the inner bottom surface of the outer shell and the gasket, the gasket, the flexible electrode and the bottom cover are in surface contact, and the conductive lead of the flexible electrode is led out from the inner cavity of the outer shell.

[0014] The technical effects of the present invention are: The flexible electrode material of the present invention adds a gallium-containing carbon particle composite material to liquid metal, thereby overcoming the difficulty that carbon particles and liquid metal are difficult to be compatible, and avoiding the corrosion of the added conductive metal by the liquid metal.

[0015] The flexible electrode material of the present invention is a liquid metal paste, which not only realizes that the liquid metal can be directly patterned, but also ensures the high conductivity of the liquid metal paste as an electrode. The liquid metal paste of the present invention is used to make a flexible electrode for preparing an electronic skin for detecting the movement state of the human body and a soil pressure gauge for detecting soil pressure in engineering, which can meet the requirements of simple preparation process, short response time, high sensitivity, high stability, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings of the present invention are as follows: Figure 1 This is a microscopic morphology of the purified carbon nanotubes prepared in Example 1; Figure 2 The microstructure and elemental energy spectrum of the gallium oxide carbon nanotube composite material prepared in Example 1; (a) and (b) Microscopic morphology of gallium oxide carbon nanotube composites; (c)-(f) Elemental energy spectra of gallium oxide carbon nanotube composites; Figure 3 The X-ray diffraction pattern of the purified carbon nanotube and gallium oxide carbon nanotube composite material prepared in Example 1; Figure 4 Conductivity curves of flexible electrodes of gallium oxide carbon nanotube composite materials and liquid metal at different contents prepared in Examples 1, 2, 3, 4, and 5; Figure 5 This is a microscopic morphology of the purified graphene prepared in Example 6; Figure 6 The microstructure and elemental energy spectrum of the gallium oxide graphene composite material prepared in Example 6; (a) and (b) Microscopic morphology of gallium oxide graphene composites; (c)-(f) Elemental energy spectra of gallium oxide graphene composites; Figure 7 The X-ray diffraction pattern of the gallium oxide graphene composite material prepared in Example 6; Figure 8 Conductivity curves of flexible electrodes of gallium oxide graphene composite materials and liquid metal at different contents prepared in Examples 6, 7, 8, 9 and 10; Fig. 9 The flexible electrode of the present invention is a preparation process of the electronic skin and the soil pressure gauge sensitive element; Fig.10 The flexible electrode of the present invention is used as electronic skin to detect the movement of human joints; Resistance response curves of (a) finger, (b) elbow, and (c) knee joint bending; (d) Schematic diagram of flexible electrodes used as electronic skin to detect different parts of human body movements; Fig.11 The flexible electrode material of the present invention is used as a sensitive element of an earth pressure gauge to monitor earth pressure; (a) Exploded view of earth pressure gauge; (b) Top view of the earth pressure gauge; (c) Front view of the earth pressure gauge; (d) Physical picture of earth pressure gauge; (e) Test curve and theoretical curve of earth pressure gauge; (f) Stability test curve of earth pressure gauge. DETAILED DESCRIPTION

[0017] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Embodiment 1: A gallium oxide carbon nanotube composite material (LMCG) comprises carbon nanotubes and gallium oxide, wherein gallium oxide is attached to the surface of the carbon nanotubes.

[0018] The following materials are measured by mass, and the preparation method of the gallium oxide carbon nanotube composite material is as follows: Step 1, purifying carbon nanotubes (MWCNTs): 2 parts of carbon nanotubes are heated in 100 parts of 3M hydrochloric acid solution through an oil bath and in a condensation reflux tube of water at room temperature to obtain purified carbon nanotubes, so as to eliminate impurities and disperse the carbon nanotubes.

[0019] The microscopic morphology of purified carbon nanotubes is shown in Figure 1 As shown, the purified carbon nanotubes are less aggregated and more dispersed.

[0020] Step 2, composite gallium oxide on the surface of carbon nanotubes: add 2 parts of purified carbon nanotubes and 2 parts of gallium chloride into 20 parts of ultrapure water, transfer to a reactor, and carry out hydrothermal reaction at 180°C for 10 hours to obtain a gallium oxide carbon nanotube composite material, and then calcine at 600°C for 2 hours in a tubular furnace under a nitrogen environment to obtain a gallium oxide carbon nanotube composite material with higher crystallinity.

[0021] The microstructure and elemental spectrum of the gallium oxide carbon nanotube composite material are described as follows Figure 2 As shown, from Figure 2 a and Figure 2 b It can be seen that a layer of material is attached to the surface of the carbon nanotubes. Further, Figure 2 c- Figure 2 The elemental energy spectrum characterization of f proves the presence of O and Ga elements in the substance. Figure 3 The X-ray diffraction patterns of purified carbon nanotubes and gallium oxide carbon nanotube composites are described. The X-ray diffractometer test proves that the material belongs to gallium oxide.

[0022] The flexible electrode material of this embodiment is a mixture of 2 parts of gallium oxide carbon nanotube composite material and 98 parts of liquid metal, and the liquid metal is gallium-indium alloy or gallium-indium-tin alloy.

[0023] The flexible electrode of this embodiment: the above-mentioned flexible electrode material is coated on a flexible substrate by screen printing, copper conductive wires are pasted on both ends of the printed flexible electrode material, viscoelastic material coating glue is coated on the surface of the flexible electrode material, and it is cured and dried at room temperature to obtain a flexible electrode.

[0024] Flexible electrode materials serve as sensitive elements of flexible electrodes.

[0025] The method for preparing the flexible electrode of this embodiment is as follows: Step A, preparing a liquid metal paste: mixing 2 parts of a gallium oxide carbon nanotube composite material and 98 parts of a liquid metal to obtain a liquid metal paste, i.e., a flexible electrode material; Step B, preparing a flexible electrode: coating the liquid metal paste on the surface of an Ecoflex 00-30 flexible substrate by screen printing to obtain a flexible electrode; Step C, making a monomer electrode: stick a conductive copper wire with a diameter of 0.05 mm to the end of the liquid metal paste, and apply an organic silicone coating glue on the surface of the liquid metal paste, and dry it at room temperature to obtain a packaged monomer electrode.

[0026] Conductivity test: Use an LCR digital bridge tester to measure the resistance of the flexible electrode. The resistance range of the LCR digital bridge is from 0 to 99.99MW. In order to evaluate the conductivity of the flexible electrode, the conductivity is calculated by the following formula: σ = L / SR In the formula, σ represents the conductivity, L represents the length of the electrode, S represents the cross-sectional area of ​​the electrode, and R represents the resistance of the electrode.

[0027] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 4 As shown, the conductivity of the flexible electrode was measured to be 3.42×10 6 S / m.

[0028] Example 2 is different from Example 1 in that: in the preparation method of the gallium oxide carbon nanotube composite material, 100 parts of 2M hydrochloric acid solution, by mass, 5 parts of carbon nanotubes, 5 parts of gallium chloride; and 100 parts of ultrapure water.

[0029] The flexible electrode material of this embodiment is a mixture of 5 parts of gallium oxide carbon nanotube composite material and 95 parts of liquid metal, by mass.

[0030] In step A, 5 parts of the gallium oxide carbon nanotube composite material and 95 parts of liquid metal are mixed to obtain a liquid metal paste.

[0031] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 4 As shown in the figure, the conductivity of the flexible electrode was measured to be 3.74×10 6 S / m.

[0032] Example 3 is different from Example 1 in that in the preparation method of the gallium oxide carbon nanotube composite material, 100 parts of 3M nitric acid solution, by mass, contain 9 parts of carbon nanotubes, 9 parts of gallium chloride, and 100 parts of ultrapure water.

[0033] The flexible electrode material of this embodiment is a mixture of 9 parts of gallium oxide carbon nanotube composite material and 91 parts of liquid metal, by mass.

[0034] In step A, 9 parts of the gallium oxide carbon nanotube composite material and 91 parts of liquid metal are mixed to obtain a liquid metal paste.

[0035] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 4 As shown in the figure, the conductivity of the flexible electrode was measured to be 3.94×10 6 S / m.

[0036] Example 4 is different from Example 1 in that in the preparation method of the gallium oxide carbon nanotube composite material, 100 parts of 2M hydrochloric acid solution, by mass, contain 14 parts of carbon nanotubes, 14 parts of gallium chloride, and 100 parts of ultrapure water.

[0037] The flexible electrode material of this embodiment is a mixture of 14 parts of gallium oxide carbon nanotube composite material and 86 parts of liquid metal, by mass.

[0038] In step A, 14 parts of the gallium oxide carbon nanotube composite material and 86 parts of liquid metal are mixed to obtain a liquid metal paste.

[0039] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 4 As shown, the conductivity of the flexible electrode was measured to be 3.15×10 6 S / m.

[0040] Example 5 is different from Example 1 in that in the preparation method of the gallium oxide carbon nanotube composite material, 100 parts of 1M nitric acid solution, by mass, contain 17 parts of carbon nanotubes, 17 parts of gallium chloride, and 100 parts of ultrapure water.

[0041] The flexible electrode material of this embodiment is a mixture of 17 parts of gallium oxide carbon nanotube composite material and 83 parts of liquid metal, by mass.

[0042] In step A, 17 parts of the gallium oxide carbon nanotube composite material and 83 parts of liquid metal are mixed to obtain a liquid metal paste.

[0043] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 4 As shown, the conductivity of the flexible electrode was measured to be 1.35×10 6 S / m.

[0044] Embodiment 6: A gallium oxide graphene composite material (LMGG) includes graphene and gallium oxide, and gallium oxide is attached to the surface of the graphene.

[0045] The following materials are measured by mass, and the preparation method of the gallium oxide graphene composite material is as follows: Step 1, purifying graphene: 2 parts of graphene are heated in 100 parts of 3M hydrochloric acid solution through an oil bath and placed in a condenser reflux tube of water at room temperature to obtain purified graphene, so as to eliminate impurities and disperse the graphene.

[0046] The microscopic morphology of purified graphene is as follows Figure 5 As shown, the purified graphene exhibits a two-dimensional layered structure with slight wrinkles between the layers, and the layers are separated and no longer tightly adhere to each other.

[0047] Step 2, composite gallium oxide on the graphene surface: add 2 parts of purified graphene and 2 parts of gallium chloride to 20 parts of ultrapure water, transfer to a reactor, and perform hydrothermal reaction at 180°C for 10 hours to obtain a gallium oxide graphene composite material, and then calcine at 600°C for 2 hours in a tubular furnace under a nitrogen environment to obtain a gallium oxide graphene composite material with higher crystallinity.

[0048] The microstructure and elemental spectrum of gallium oxide graphene composite materials are described as follows Figure 6 As shown, from Figure 6 a and Figure 6 b It can be seen that a layer of material is attached to the surface of the carbon nanotubes. Further, Figure 6 c- Figure 6 The elemental energy spectrum characterization of f proves the presence of O and Ga elements in the substance. Figure 7 The X-ray diffraction pattern of the gallium oxide graphene composite material is described, and it can be proved that the material belongs to gallium oxide through X-ray diffractometer testing.

[0049] The flexible electrode material of this embodiment is a mixture of 2 parts of gallium oxide graphene composite material and 98 parts of liquid metal, and the liquid metal is a gallium-indium alloy or a gallium-indium-tin alloy.

[0050] The flexible electrode of this embodiment: the above-mentioned flexible electrode material is coated on a flexible substrate by screen printing, copper conductive wires are pasted on both ends of the printed flexible electrode material, viscoelastic material coating glue is coated on the surface of the flexible electrode material, and it is cured and dried at room temperature to obtain a flexible electrode.

[0051] The method for preparing the flexible electrode of this embodiment is as follows: Step A, preparing a liquid metal paste: mixing 2 parts of the gallium oxide graphene composite material and 98 parts of liquid metal to obtain a liquid metal paste, i.e., a flexible electrode material; Step B, preparing a flexible electrode: coating the liquid metal paste on the surface of an Ecoflex 00-30 flexible substrate by screen printing to obtain a flexible electrode; Step C, making a monomer electrode: stick a conductive copper wire with a diameter of 0.05 mm to the end of the liquid metal paste, and apply an organic silicone coating glue on the surface of the liquid metal paste, and dry it at room temperature to obtain a packaged monomer electrode.

[0052] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 8 As shown in the figure, the conductivity of the flexible electrode was measured to be 3.65×10 6 S / m.

[0053] Example 7 is different from Example 6 in that: in the preparation method of the gallium oxide graphene composite material, 100 parts of 2M hydrochloric acid solution, by mass, 5 parts of graphene, 5 parts of gallium chloride; and 100 parts of ultrapure water.

[0054] The flexible electrode material of this embodiment is a mixture of 5 parts of gallium oxide graphene composite material and 95 parts of liquid metal, by mass.

[0055] In step A, 5 parts of the gallium oxide graphene composite material and 95 parts of liquid metal are mixed to obtain a liquid metal paste.

[0056] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 8 As shown in the figure, the conductivity of the flexible electrode was measured to be 3.89×10 6 S / m.

[0057] Example 8 is different from Example 6 in that: in the preparation method of the gallium oxide graphene composite material, 100 parts of 2M hydrochloric acid solution, by mass, contain 9 parts of graphene, 9 parts of gallium chloride, and 100 parts of ultrapure water.

[0058] The flexible electrode material of this embodiment is a mixture of 9 parts of gallium oxide graphene composite material and 91 parts of liquid metal, by mass.

[0059] In step A, 9 parts of the gallium oxide graphene composite material and 91 parts of liquid metal are mixed to obtain a liquid metal paste.

[0060] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 8 As shown, the conductivity of the flexible electrode was measured to be 3.20×10 6 S / m.

[0061] Example 9 is different from Example 6 in that: in the preparation method of the gallium oxide graphene composite material, 100 parts of 2M hydrochloric acid solution, by mass, contain 14 parts of graphene, 14 parts of gallium chloride, and 100 parts of ultrapure water.

[0062] The flexible electrode material of this embodiment is a mixture of 14 parts of gallium oxide graphene composite material and 86 parts of liquid metal, by mass.

[0063] In step A, 14 parts of the gallium oxide graphene composite material and 86 parts of liquid metal are mixed to obtain a liquid metal paste.

[0064] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 8 As shown, the conductivity of the flexible electrode was measured to be 2.78×10 6 S / m.

[0065] Example 10 is different from Example 6 in that in the preparation method of the gallium oxide graphene composite material, 100 parts of 2M hydrochloric acid solution, by mass, contain 17 parts of graphene, 17 parts of gallium chloride, and 100 parts of ultrapure water.

[0066] The flexible electrode material of this embodiment is a mixture of 17 parts of gallium oxide graphene composite material and 83 parts of liquid metal, by mass.

[0067] In step A, 17 parts of the gallium oxide graphene composite material and 83 parts of liquid metal are mixed to obtain a liquid metal paste.

[0068] The resistance and conductivity test of the flexible electrode of this embodiment is as follows: Figure 8 As shown, the conductivity of the flexible electrode was measured to be 2.15×10 6 S / m.

[0069] Application Example 1: In order to explore the application potential of the above-mentioned flexible electrode, the flexible electrode of Example 3 is used as an electronic skin to monitor the state of human movement. A series circuit is formed by a metal wire and an LCR digital bridge tester, and then the electronic skin is fixed to various joints, and the resistance change of the flexible large strain sensor to the movement of the joint is recorded.

[0070] The production process of electronic skin is as follows Fig. 9 As shown, the liquid metal paste (flexible electrode material) obtained by mixing the gallium oxide carbon nanotube composite material with the liquid metal is coated on the Ecoflex 00-30 substrate by screen printing; a copper conductive wire with a diameter of 0.05 mm is pasted on the end of the paste, and a silicone coating glue is coated on the surface of the liquid metal paste to protect the paste from external interference; it is cured and dried at room temperature to obtain an electronic skin with a length of 60 mm, a width of 45 mm, and a height of 5 mm.

[0071] Skin strain sensors are verified by fixing the prepared electronic skin on various joints and monitoring the strain signals generated by human body movements. Metal wires are fixed to the two ends of the flexible electrodes. The electronic skin can monitor the fingers, wrists, elbows and knees. The two ends of the electronic skin are fixed to the human body with tape to detect the strain information of the bending of each joint.

[0072] like Fig.10 As shown, the electronic skin is able to generate corresponding signals when these joints move, and it is repeatable. Fig.10 In (a), as the subject's wrist bending degree increases, the relative resistance change rate RRC of the electronic skin (RRC=△R / R 0 , △R represents the resistance change, R 0 represents the initial resistance) will also increase accordingly, and the RRC of the electronic skin remains unchanged at a fixed bending degree. Fig.10 (b) and Fig.10 In (c), when the subject's elbow and knee joints are bent, the RRC in the electronic skin increases accordingly with the change in the length and cross-sectional area of ​​the electrodes; after the calf is extended, the electronic skin quickly restores its output to its original state; when the knee joint is fully bent again, the electronic skin can accurately and quickly detect the signal of repetitive motion. The above tests prove that electronic skin can be used to detect motion signals of human joints.

[0073] Application Example 2: Using the flexible electrode of Example 7 to monitor the soil pressure of an engineering project, a soil pressure gauge (soil pressure sensor) is manufactured. Fig.11 (a) to Fig.11 As shown in (d): The soil pressure gauge includes a cylindrical shell 1, a connecting cylinder 3, a gasket 2, a flexible electrode 4 and a bottom cover 5 which are arranged in sequence from top to bottom in the inner cavity of the shell 1. The connecting cylinder 3 is located in the center between the inner bottom surface of the shell 1 and the gasket 2. The gasket 2, the flexible electrode 4 and the bottom cover 5 are in surface contact. The conductive lead 44 of the flexible electrode 4 is led out from the inner cavity of the shell 1.

[0074] The dimensions of the stainless steel housing 1 are 5mm thick on the side wall, 1mm thick on the top, 20mm high, and 70mm in inner diameter; the stainless steel gasket 2 is subjected to deflection, and is 3mm thick and 69.6mm in outer diameter; the connecting cylinder 3 is the fulcrum of the center of the gasket, and is 4mm high and 4mm in diameter; the flexible electrode 4 is used as a sensor, and is 49mm long, 49mm wide, and 5mm high; the dimensions of the stainless steel bottom cover 5 are 5mm thick and 70mm in outer diameter. The flexible electrode 4 uses a paste mixed with a graphene composite material and liquid metal as a flexible electrode material, and the printed and coated flexible trace 42 is 231mm long, 3mm wide, and 1mm high. The bottom surface of the flexible trace 42 is a soft substrate 43, and a layer of organic silicon 41 is coated on the flexible trace 42. Conductive leads 44 are attached to both ends of the flexible trace 42. Fig.11 The bottom boss of c can be twisted to screw the bottom cover, which is surrounded by threads. There is a screw sleeve on the inner side of the earth pressure gauge shell, and the bottom cover can be screwed up to support the flexible electrode 4.

[0075] The thickness of the side wall of the stainless steel shell is set to 5mm to ensure that the side wall of the sensor is not affected by the side wall pressure. The working principle of the soil pressure gauge: the soil pressure is applied to the top surface of the stainless steel shell, and is transmitted to the stainless steel gasket 2 through the connecting cylinder 3, causing the stainless steel gasket to displace. The displacement is applied to the sensitive element 4 made of flexible electrode, and the flexible trace line 44 inside the sensitive element is squeezed, causing the resistance to change. The RRC of the sensitive element made of flexible electrode and the theoretical predicted value of the external applied pressure ( Fig.11 e) and the experimental measurements ( Fig.11 e's triangle symbol and inverted triangle symbol) such as Fig.11 e. The change of RRC increases linearly with the applied pressure, and the average value curve ( Fig.11 The fitting of the blue dashed line in e) is highly similar to the theoretical prediction. The value of the error spline is the standard deviation of the RRC of the sample under five measurements, indicating that the sensitive element has significant repeatability and low hysteresis. The RRC measured under different pressures is shown in Fig.11 f, each loading lasted for 15 minutes and readings were recorded every 3 minutes. The maximum relative standard deviation of the test results (RSD = 3.1%) proved that the earth pressure gauge has high mechanical durability.

Claims

1. A carbon particle composite material, characterized in that: The invention comprises carbon particles and gallium oxide, wherein gallium oxide is attached to the surface of the carbon particles, and the carbon particles are carbon nanotubes or graphene.

2. A method for preparing a carbon particle composite material, characterized in that: The following steps are involved: Step 1, purifying carbon particles: heating carbon particles in an acidic solution through an oil bath and obtaining purified carbon particles in a condensation reflux tube of water at room temperature to eliminate impurities and disperse the carbon particles; Step 2, composite gallium oxide on the surface of carbon particles: add purified carbon particles and gallium chloride into ultrapure water, transfer to a reactor for hydrothermal reaction to obtain a gallium oxide carbon nanotube composite material, and then calcine in a tubular furnace under a nitrogen environment to obtain a gallium oxide carbon particle composite material with higher crystallinity.

3. The method for preparing the carbon particle composite material according to claim 2, characterized in that: The acid solution is a nitric acid solution or a hydrochloric acid solution, and the hydrogen ion concentration is 1M to 3M.

4. A flexible electrode material, comprising the carbon particle composite material according to claim 1, characterized in that: A mixture of 2 to 17 parts by mass of a carbon particle composite material and 83 to 98 parts by mass of a liquid metal, wherein the liquid metal is a gallium-indium alloy or a gallium-indium-tin alloy.

5. A flexible electrode prepared using the flexible electrode material according to claim 4, characterized in that: The flexible electrode material is coated on a flexible substrate by screen printing, wires are attached to both ends of the printed flexible electrode material, a viscoelastic material coating glue is coated on the surface of the flexible electrode material, and the material is cured and dried at room temperature to obtain a flexible electrode.

6. A method for preparing a flexible electrode according to claim 5, characterized in that: The following steps are involved: Step A, preparing a liquid metal paste: mixing 2 to 17 parts by mass of a carbon particle composite material and 83 to 98 parts by mass of a liquid metal to obtain a liquid metal paste; Step B, preparing a flexible electrode: coating the liquid metal paste on the surface of a flexible substrate by screen printing to obtain a flexible electrode; Step C, making a single electrode: sticking a wire to the end of the liquid metal paste, coating a viscoelastic material on the surface of the liquid metal paste, and drying at room temperature to obtain a packaged single electrode.

7. The flexible electrode according to claim 5 is used as electronic skin to detect the movement state of a human body.

8. The flexible electrode according to claim 5 is used as a sensitive element of an earth pressure gauge to measure earth pressure.

9. An earth pressure gauge, characterized in that: The invention comprises a cylindrical shell (1), a connecting cylinder (3), a gasket (2), the flexible electrode (4) according to claim 5 and a bottom cover (5) which are arranged in sequence from top to bottom in the inner cavity of the shell (1), wherein the connecting cylinder (3) is located at the center between the inner bottom surface of the shell (1) and the gasket (2), the gasket (2), the flexible electrode (4) and the bottom cover (5) are in surface contact, and the conductive lead (44) of the flexible electrode (4) is led out from the inner cavity of the shell (1).